Multimodal on BPJS Ads "The Dangers of Playing Firecrackers" on the Detik.com - Muhammad Zuhra Trianggawan; M. Yoserizal Saragih (LEGAL BRIEF, 2022)
The purpose of this research is to examine the multimodal advertisement for BPJS's "Bahaya Main Firecracker," which was published on the detik.com online news site. The multimodal analysis was conducted using two criteria: linguistic and visual. This study employs Halliday's SFL theory for linguistic analysis, and Kress and Van Leuwen's theory for visual analysis. The descriptive qualitative research method is used in this study, along with the documentation technique. The interactive mode developed by Miles and Huberman was used in this study as a data analysis technique. After analyzing the data, it is discovered that the characters in the advertisement use a variety of sentences. Children who have been injured by firecrackers use the existence of imperative sentences to express their pain. The victim's father, as the party responsible for the victim, used interrogative sentences to ask the doctor several questions about health insurance. Meanwhile, affirmative sentences were delivered by doctors who served as resource persons, explaining the injuries caused by firecrackers and the health insurance provided by BPJS. The transitivity system in SFL differs between these three sentence forms. On the other hand, the visual analysis results show that there is an appearance in the advertisement that contradicts the illustration of a doctor being a doctor. The use of short but meaningful language combined with expressive images piques the reader's interest in reading the entire ad. As a result, it is possible to conclude that the visualization in this public service advertisement is contentious because it does not correspond to current reality.